Religion, Discrimination and Trust - Swee Hoon Chuah; Simon Gächter; Robert Hoffmann; Jonathan H. W. Tan (Institute for the Study of Labor (IZA), 2015)
We propose that religion impacts trust and trustworthiness in ways that depend on how individuals are socially identified and connected. Religiosity and religious affiliation may serve as markers for statistical discrimination. Further, affiliation to the same religion may enhance group identity, or affiliation irrespective of creed may lend social identity, and in turn induce taste-based discrimination. Religiosity may also relate to general prejudice. We test these hypotheses across three culturally diverse countries. Participants' willingness to discriminate, beliefs of how trustworthy or trusting others are, as well as actual trust and trustworthiness are measured incentive compatibly. We find that interpersonal similarity in religiosity and affiliation promote trust through beliefs of reciprocity. Religious participants also believe that those belonging to some faith are trustworthier, but invest more trust only in those of the same religion – religiosity amplifies this effect. Across non-religious categories, whereas more religious participants are more willing to discriminate, less religious participants are as likely to display group biases.
Keywords: C72; C91; J16; Z12; 330; religiosity; connectedness; discrimination; trust; experiment